Meat-Eating and Jewish Identity: Ritualization of the Priestly “Torah of Beast and Fowl” (Lev 11:46) in Rabbinic Judaism and Medieval Kabbalah - Brumberg-Kraus, Jonathan (AJS review, 1999)
In a fascinating chapter dealing with the “nature of eating” in Shulhan shel Arba, a short thirteenth-century manual on rabbinic eating rituals, R. Bahya b. Asher suggests that Torah scholars alone are fit to eat meat, based on the following passage from the Talmud: “it is forbidden for an ignoramus [am ha-aretz] to eat meat, as it is written, ‘This is the torah of beast and fowl’ (Lev 11:46); for all who engage in Torah, it is permitted to eat the flesh of beast and fowl. This passage raises many questions, especially for a vegetarian! First, why would an intellectual or spiritual elite use meat-eating as a way to distinguish itself from the masses? The field of comparative religions offers many counter-examples to this tendency: the vegetarian diet of the Hindu Brahmin caste, of Buddhist priests and nuns, the ancient Pythagoreans, the Neoplatonist regimen advocated by Porphyry in On Abstinence, or even contemporary eco-theologians, animal rights activists, and feminist vegetarians like Carol Adams.